2014
DOI: 10.1103/physreve.89.032921
|View full text |Cite
|
Sign up to set email alerts
|

Finite-time synchronization of tunnel-diode-based chaotic oscillators

Abstract: This paper addresses the problem of finite-time synchronization of tunnel diode based chaotic oscillators. After a brief investigation of its chaotic dynamics, we propose an active adaptive feedback coupling which accomplishes the synchronization of tunnel-diode-based chaotic systems with and without the presence of delay(s), basing ourselves on Lyapunov and on Krasovskii-Lyapunov stability theories. This feedback coupling could be applied to many other chaotic systems. A finite horizon can be arbitrarily esta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…These graphs show that the numerical finite-time of synchronization is t q rN U = 0.2 μs, which respects the finite-time condition t rN U ≤ t rT H [47]. Figure 5c gives the time evolution of the adaptive feedback controller u(t) which exponentially decreases towards a stable state just before the numerical finite-time synchronization t rN U is reached.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…These graphs show that the numerical finite-time of synchronization is t q rN U = 0.2 μs, which respects the finite-time condition t rN U ≤ t rT H [47]. Figure 5c gives the time evolution of the adaptive feedback controller u(t) which exponentially decreases towards a stable state just before the numerical finite-time synchronization t rN U is reached.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…In the present paper, based on the Lyapunov function a fractional adaptive finite-time synchronization reflecting the method in [47] is proposed for fractional-order versions of the circuit in [43]. Then, a new key system for encryption on digital cryptography is found, using the proposed finite-time synchronization scheme which is more secure and more powerful than an existing key system of integerorder synchronization [22].…”
Section: Introductionmentioning
confidence: 99%
“…According to J. C. Sprott, the part of the controller in brown box (Fig. 6), simulates the absolute value function; the sign function is simulated by the part in the orange box, of the same figure (Sprott 2000;Louodop et al 2014). With the help of the Kirchhoff law, and taking into account that the operational amplifiers are ideal devices, the states of the whole network satisfy the set of nonlinear differential equations: 2.…”
Section: Electronic Implementation Of the Synchronization Scheme And mentioning
confidence: 99%
“…Due to its diverse applications, synchronization phenomenon in complex network has attracted great attentions (Motter et al 2006;Restrepo et al 2006;Arenas et al 2006;Chen and Zhou 2006;Bowong andKakmeni 2004, 2003;Fotsin and Daafouz 2005;Louodop et al 2013;Tchitnga et al 2013;Louodop et al 2014;Megam et al 2014b, a). Controlled synchronization, with the aim of imposing a desired behavior to a member of a network and then inferring the same behavior in the whole network, represents a recent problem in complex networks (CornejoPerez et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the phenomenon is not system specific restricted to these jerk systems only, but generic. We investigated other examples [23][24][25][26], the paradigmatic Rössler system, a coupled tunnel diode model, and a Josephson junction-based jerk model. In all of them, we observed coherent motion, but the exchange of leadership appears only for the Josephson junction-based jerk model, apart from the one described in this manuscript (details can be seen in the Appendices A, B, and C).…”
Section: Discussionmentioning
confidence: 99%